UPAYA PELAYANAN PASTORAL DI STASI SANTO MIKAEL SAKAN UNTUK MENINGKATKAN KETERLIBATAN UMAT - Sinulingga, Aldi Alfrianza; Else, Marsela (STP St. Bonaventura Medan, 2019)
This research aims to describe efforts to activate the congregation in participating in the Sunday Word celebration without a priest through pastoral care at St. Michael's Station in the Parish of Santa Maria Bunda Allah Nanga Mahap, Sanggau Diocese. The background of this research is that Sunday is a sacred day for God, where in the Word celebration when the Scriptures are read, God is present among His people. The presence of God in the Sunday Word celebration invites the congregation to be present and actively participate in achieving holiness. In reality, many Catholic faithful are less active in the Word celebration. This is evident among the Catholic community at St. Michael's Station in the Parish of Santa Maria Bunda Allah. The congregation in St. Michael's Station is often less active in participating in the Sunday Word celebration. Based on this situation, the researcher feels the need for pastoral guidance for the congregation. Pastoral care is an effort to build or nurture the faith community. Pastoral guidance is carried out to help the congregation understand their calling as the people of God. This research uses the action research method. Data collection techniques include observation and interviews. The collected data is then reduced, analyzed, and tested for validity through source triangulation. The results of the research show that the attendance of the congregation in the Sunday Word celebration without a priest at St. Michael's Station in the Parish of Santa Maria Bunda Allah is still limited. The factors causing the congregation to be less active in participating in the Sunday Word celebration without a priest are the lack of awareness of the congregation in living a church-centered life, the lack of appreciation for the Word celebration among the congregation, and the lack of faith formation